A Review on the Update of Combined Hepatocellular Cholangiocarcinoma - Komuta, Mina; Yeh, Matthew M. (Seminars in Liver Disease, 2020)
Combined hepatocellular-cholangiocarcinoma (cHCC-CCA) is a primary liver tumor with neoplastic components of both hepatocytic and cholangiocytic differentiation. This unique neoplasm is gaining increasing recognition due to the intriguing pathology, tumor biology, and clinical behavior. It also poses challenges in diagnosis, treatment, and research, largely because of its histological and phenotypic diversity that lead to confusion in terminology and classification. There have been efforts attempting to unify the terminology of this neoplasm recently. Advances in investigation in various aspects have also been made. This review aims to update the terminology, classification, and clinical and pathological characteristics of cHCC-CCA.
Keywords: combined hepatocellular carcinoma-cholangiocarcinoma; hepatocytic; cholangiocytic